The Influence of Inclusive Instagram Content by Raecca on Followers' Purchase Intention Mediated by Their Attitude - Syakira, Raden Zata; Gracia, Amanda Bunga (eProceedings of Management, 2025)
In today's digital age, where consumers are increasingly aware of social issues and marketing authenticity, the beautyindustry faces mounting pressure to deliver inclusive and credible brand communication. This study examines theinfluence of inclusive Instagram content on purchase intention, with consumer attitude as a mediating variable, usingthe Theory of Reasoned Action (TRA) as the theoretical framework. TRA posits that behavior is driven by intention,which in turn is shaped by attitudes and subjective norms. Focusing on Raecca, an Indonesian beauty brand knownfor its bold stance on inclusivity, this research investigates whether inclusive and diverse content on Instagramtranslates into favorable consumer behavior. This research uses quantitative methods with the type of explanatorycorrelation research. Sampling was carried out using the nonprobabilty sampling type purposive sampling. The dataanalysis technique used is descriptive analysis and partial least square-structural equation modeling (PLS-SEM)using SmartPLS 3. The results reveal that inclusive content has a strong positive influence on consumer attitudes (pathcoefficient = 0.920), inclusive content has moderate positive influence on purchase intention (0.595), and consumerattitude also significantly influences purchase intention (0.340). Furthermore, attitude partially mediates therelationship between inclusive content and purchase intention (indirect effect = 0.313). These results highlight thatwhile inclusivity is impactful, its effectiveness hinges on authenticity. Thus, the study underscores the importance forbeauty brands to not only adopt inclusive narratives but to authentically embed these values in their identity andmarketing strategies.Social media marketing, inclusive content, consumer attitude, purchase intention, Theory of Reasoned Action